Role of P53 Expression in Pterygium in Natives from Hilly Area - Sanjay, Kaushik; Brijesh, Thakur; Sanjeev, Kishore; Pooja, Kala (Annals of Pathology and Laboratory Medicine, 2018)
BACKGROUND: Pterygium has been considered an ocular degenerative fibrovascular neoformation for long but abnormal p53 expression reinforces the theory that it is a proliferative condition like a tumor. The present study was aimed to describe the pattern of p53 immunoexpression in pterygium. MATERIAL AND METHODS: We included 50 excised pterygium and 10 normal conjunctival control specimens, processed for histopathology and immunostaining for p53. Cut-off value of p53 expression was taken as 5% epithelial cell positivity. RESULTS: We found higher incidence of pterygium in females and statistically significant positive p53 expression in 38 cases (76%) as compared to control group. No significant association between variations in clinical grade or histological features and abnormal p53 expression in cases and control groups was found. CONCLUSION: p53 overexpression in pterygium suggests that pterygium is a proliferative tissue disorder.